The Influence of Trust, Price, and Brand Ambassador on Purchase Decisions on The Shopee Platform Among Tri Bhakti Students - Maulida, Sofia; Falqi, Sarah Maulidah (Yayasan Gema Bina Nusantara, 2025)
The purpose of this study is to ascertain how trust, price, and brand ambassadors affect Shopee platform purchasing decisions, particularly among Tri Bhakti students. 84 respondents were given questionnaires as part of a quantitative survey technique. Multiple linear regression was used to analyze the data. Because the trust variable's significance value is 0.000 < 0.05 and its t-table value is 1.990 <t-count value of 6.153, the results of the partial test (t-test) study demonstrate that the trust variable significantly influences purchasing decisions. The price variable has a substantial impact on purchase decisions, according to the partial test (t-test), with a significant value of 0.029 < 0.05 and a t-count value of 2.228. With a significance value of 0.452 > 0.05 and a t-table value of 1.990 < t-count value of 0.755, the partial test (t-test) indicates that the brand ambassador variable has no meaningful impact on purchasing decisions. The simultaneous test findings (f test). With a significance level of 0.000 < 0.05, the computed F value of 31.752 is higher than the F table of 2.72, indicating that the three independent factors concurrently have a considerable impact on purchase decisions.